2015
DOI: 10.1016/j.nicl.2015.06.007
|View full text |Cite
|
Sign up to set email alerts
|

Altered whole-brain white matter networks in preclinical Alzheimer's disease

Abstract: Surrogates of whole-brain white matter (WM) networks reconstructed using diffusion tensor imaging (DTI) are novel markers of structural brain connectivity. Global connectivity of networks has been found impaired in clinical Alzheimer's disease (AD) compared to cognitively healthy aging. We hypothesized that network alterations are detectable already in preclinical AD and investigated major global WM network properties. Other structural markers of neurodegeneration typically affected in prodromal AD but seeming… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
71
1
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 89 publications
(81 citation statements)
references
References 49 publications
8
71
1
1
Order By: Relevance
“…The progress of neuroimaging techniques, in particular diffusion magnetic resonance imaging (dMRI) and functional MRI, as well as post-processing (tractography) and network analysis methods, has enabled the in vivo study of the structural and functional connectivity that form the brain connectome. Connectomics has so far confirmed the impairment of network connectivity in AD observed by neuroanatomical and neuropathological studies, supporting the role of white matter degeneration in the disease, and the fact that part of the symptoms are due to disconnection of distant cortical regions (Daianu et al, 2013b(Daianu et al, , 2013aFischer et al, 2015;Mallio et al, 2015;Nir et al, 2012Nir et al, , 2015Prescott et al, 2014).…”
Section: Introductionmentioning
confidence: 74%
“…The progress of neuroimaging techniques, in particular diffusion magnetic resonance imaging (dMRI) and functional MRI, as well as post-processing (tractography) and network analysis methods, has enabled the in vivo study of the structural and functional connectivity that form the brain connectome. Connectomics has so far confirmed the impairment of network connectivity in AD observed by neuroanatomical and neuropathological studies, supporting the role of white matter degeneration in the disease, and the fact that part of the symptoms are due to disconnection of distant cortical regions (Daianu et al, 2013b(Daianu et al, , 2013aFischer et al, 2015;Mallio et al, 2015;Nir et al, 2012Nir et al, , 2015Prescott et al, 2014).…”
Section: Introductionmentioning
confidence: 74%
“…Neurodegenerative processes affect modular networks rather than isolated regions (16). Long-distance interregional metabolic correlations are impaired by the anatomofunctional progression of neuronal and white matter fiber degeneration (17), causing local compensatory networks to take over and increasing the anatomic and functional segregation of brain processes.…”
Section: Discussionmentioning
confidence: 99%
“…Also, the number of voxels composing the independent components progressively increased from control subjects (17,491) to AD patients (51,740). We highlight here only the independent components with pathophysiologic significance, and the brain regions included in them (Table 2).…”
Section: Icamentioning
confidence: 99%
“…Regions less connected were less likely to aggregate amyloid. (Fischer et al, 2015) DTI, Amyloid-PET Graph-theoretical measures of structural connectivity revealed significant group differences between 31 amyloid-negative cognitively healthy subjects vs. 12 amyloid-positive cognitively healthy subjects.…”
Section: Dti + (Amyloid-pet/fdg-pet)mentioning
confidence: 92%
“…In AD dementia, structural connectivity networks exhibit altered topological network metrics, such as increased shortest path lengths, decreased local and global efficiency, and decreased number of rich-club hub nodes (Daianu et al, 2013(Daianu et al, , 2015Lo et al, 2010;Shao et al, 2012). These topological network changes were also shown to account for core memory and executive function deficits (Reijmer et al, 2013), and were already detectable in cognitively normal individuals with high amyloid burden (Fischer, Wolf, Scheurich, & Fellgiebel, 2015) and asymptomatic APOE4 carriers (Brown et al, 2011). However, current DTI-based fiber tracking algorithms are limited in their ability to resolve crossing and touching fiber bundles, which are highly prevalent fiber configurations in the human white matter (Jeurissen, Leemans, Tournier, Jones, & Sijbers, 2013).…”
Section: Structural Disconnection In the Course Of Admentioning
confidence: 99%